Diabetic Myonecrosis: Uncommon Complications in Common Diseases - Sran, Sisira (Hindawi Publishing Corporation, 2014)
We report a case of sudden thigh pain from spontaneous quadriceps necrosis, also known as diabetic myonecrosis, in a 28-year-old patient with poorly controlled diabetes mellitus. Diabetic muscle infarction is a rare end-organ complication seen in patients with poor glycemic control and advanced chronic microvascular complications. Proposed mechanisms involve atherosclerotic microvascular occlusion, ischemia-reperfusion related injury, vasculitis with microthrombi formation, and an acquired antiphospholipid syndrome. Diabetic myonecrosis most commonly presents as sudden thigh pain with swelling and should be considered in any patient who has poorly controlled diabetes mellitus.